2023
DOI: 10.1530/joe-23-0026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peripheral neural stimulation with allopregnanolone on ovarian physiology

Abstract: Neuroactive steroids can rapidly regulate multiple physiological functions on the central and peripheral nervous systems. The aims of the present study were to determine whether allopregnanolone (ALLO), administered in a low nanomolar and a high micromolar concentrations, can: a) induce changes in the ovarian progesterone (P4) and estradiol (E2) release, b) modify the ovarian mRNA expression of 3 β-HSD, 20 α-HSD and 3 α-HSD, c) modulate the ovarian expression of progesterone receptors A and B, α and β estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The ALLO concentration of 6 µM was chosen for these studies based on a concentration–response curve (data not shown) and previous works. It was the pharmacological concentration with the greatest effects on ovarian physiology 19 , 22 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ALLO concentration of 6 µM was chosen for these studies based on a concentration–response curve (data not shown) and previous works. It was the pharmacological concentration with the greatest effects on ovarian physiology 19 , 22 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it can modulate a variety of behaviors, such as reproductive 10 13 , social, exploratory and affective conducts 14 16 . Previous work from our laboratory reported ALLO actions over the hypothalamic–pituitary–gonadal axis when administered via ICV 17 19 and its effects on the ovarian peripheral innervation using an ex vivo culture of the superior mesenteric ganglion- ovarian nervous plexus—ovarian system 20 22 . These findings led us to consider ALLO not only as a modulator of central function but also of ovarian physiology.…”
Section: Introductionmentioning
confidence: 99%